2014
DOI: 10.1093/jb/mvu026
|View full text |Cite
|
Sign up to set email alerts
|

Self-propagating amyloid as a critical regulator for diverse cellular functions

Abstract: Amyloids are β-sheet-rich fibrillar protein aggregates characterized by structural properties of self-propagation and strong resistance to detergent and proteinase. Although a number of causative proteins for neurodegenerative disorders are known to undergo amyloid formation, recent studies have revealed that amyloids may also play beneficial roles in cells. Cellular processes that could be regulated by amyloids are diverse and include translational regulation, programmed cell death and protein storage. Yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Although we focus this review on disease mechanisms, the discovery that prion-like processes govern heritable traits in certain fungi opened a rich and productive field of research that has yielded invaluable insights into the biology of prions (Krauss & Vorberg 2013, Liebman & Chernoff 2012, Newby & Lindquist 2013, Prusiner 2013, Sugiyama & Tanaka 2014, Tuite 2013, Wickner et al 2013). Prion-like processes also appear to influence functional protein aggregation in such phenomena as memory formation (Raveendra et al 2013, Si et al 2003), peptide storage (Maji et al 2009), and the innate immune response (Cai et al 2014, Hou et al 2011) and inflammation (Franklin et al 2014).…”
Section: Prion-like Processes Beyond the Nervous Systemmentioning
confidence: 99%
“…Although we focus this review on disease mechanisms, the discovery that prion-like processes govern heritable traits in certain fungi opened a rich and productive field of research that has yielded invaluable insights into the biology of prions (Krauss & Vorberg 2013, Liebman & Chernoff 2012, Newby & Lindquist 2013, Prusiner 2013, Sugiyama & Tanaka 2014, Tuite 2013, Wickner et al 2013). Prion-like processes also appear to influence functional protein aggregation in such phenomena as memory formation (Raveendra et al 2013, Si et al 2003), peptide storage (Maji et al 2009), and the innate immune response (Cai et al 2014, Hou et al 2011) and inflammation (Franklin et al 2014).…”
Section: Prion-like Processes Beyond the Nervous Systemmentioning
confidence: 99%
“…Amyloid fibrils are linked to a broad range of human diseases [1]. In the last decade, a growing body of evidence demonstrated that in some organisms amyloid structures could also play important "beneficial" functional roles [2][3][4][5][6][7]. Typically, the amyloid fibrils consist of multiple copies of the same protein.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, prion formation or loss can be facilitated by environmental stresses including heat shock (Newnam et al, 2011; Tuite et al, 1981; Tyedmers et al, 2008). It has been hypothesized that transient prion-like states could be acquired in response to stress, where their presence could be protective, and lost after these conditions have passed, although selfish or pathogenic self-perpetuating prions may remain as by-products of this process (Chernoff, 2007; Halfmann and Lindquist, 2010; Li and Kowal, 2012; Sugiyama and Tanaka, 2014). Prions whose biological effect depends on growth conditions include [ MOT3 + ], which regulates expression of the genes affecting cell wall biogenesis and leads to filamentous growth and increased ethanol resistance (Holmes et al, 2013) and [ MOD + ], a prion isoform of an RNA modification enzyme that results in increased levels of intracellular ergosterol and resistance to inhibitors of ergosterol synthesis such as the common antifungal drugs fluconazole and ketoconazole, (Suzuki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%